Effects of plyometric jump training on measures of physical fitness and lower-limb asymmetries in male soccer players according to maturity: A randomized controlled trial - Nizar Bouafif; Roland van den Tillaar; Abdelkader Mahmoudi; Anis Chaouachi; Raouf Hammami (PLoS ONE, 2026)
The purpose of this study was to determine the effects plyometrics on dynamic balance, muscle power and lower limb asymmetries in youth soccer players according to maturity. 43 youth soccer players (23 pre pubertal and 20 post pubertal) were classified according to their peak height velocity (PHV) and participated in a 8-week progressive plyometrics training program or an active control with two weekly sessions, alongside three regular soccer-specific training sessions per week. Participants’ training and performance caliber was rated Tier 2. While plyometrics training groups performed jumping and hopping exercises such as maximal and submaximal hopping on stable ground, active control groups performing passing skills. Pre and post training, tests included the Y balance test, single leg hop and 505 change-of-direction speed (CoD) tests; and lower limb asymmetries were calculated based upon these tests. The main findings were that plyometrics significantly improved these physical attributes, with greater enhancements observed in the post-Peak Height Velocity (PHV) group compared to both the pre-PHV group and the active control group. However, asymmetry did not improve after the training intervention and even increased for balance test in the post-PHV training groups compared with the pre-PHV groups at the post test. Plyometrics effectively enhances jumps, CoD and dynamic balance, with greater benefits observed in post- PHV male soccer players. While overall lower-limb asymmetry largely remained unchanged, a notable finding was an increase in balance asymmetry specifically within the post-PHV group, attributed to a differential enhancement of left and right limb balance.